Spectrum of MEK1 and MEK2 gene mutations in cardio-facio-cutaneous syndrome and genotype–phenotype correlations - Dentici, Maria Lisa (Nature Publishing Group, 2009)
Cardio-facio-cutaneous syndrome (CFCS) is a rare disease characterized by mental retardation, facial dysmorphisms, ectodermal abnormalities, heart defects and developmental delay. CFCS is genetically heterogeneous and mutations in the KRAS, BRAF, MAP2K1 (MEK1) and MAP2K2 (MEK2) genes, encoding for components of the RAS–mitogen activated protein kinase (MAPK) signaling pathway, have been identified in up to 90% of cases. Here we screened a cohort of 33 individuals with CFCS for MEK1 and MEK2 gene mutations to further explore their molecular spectrum in this disorder, and to analyze genotype–phenotype correlations. Three MEK1 and two MEK2 mutations were detected in six patients. Two missense MEK1 (L42F and Y130H) changes and one in-frame MEK2 (K63_E66del) deletion had not been reported earlier. All mutations were localized within exon 2 or 3. Together with the available records, the present data document that MEK1 mutations are relatively more frequent than those in MEK2, with exons 2 and 3 being mutational hot spots in both genes. Mutational analysis of the affected MEK1 and MEK2 exons did not reveal occurrence of mutations among 75 patients with Noonan syndrome, confirming the low prevalence of MEK gene defects in this disorder. Clinical review of known individuals with MEK1/MEK2 mutations suggests that these patients show dysmorphic features, ectodermal abnormalities and cognitive deficit similar to what was observed in BRAF-mutated patients and in the general CFCS population. Conversely, congenital heart defects, particularly mitral valve and septal defects, and ocular anomalies seem to be less frequent among MEK1/MEK2 mutation-positive patients.